Being fashion smart : the textiles industry at Premiere Vision - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (London : SAGE Publications Ltd, 2017)
Founded in 1956, Akin Tekstil is a textile manufacturer with production facilities at three different locations in Turkey. The company's activities cover different stages of the textiles value chain, from the spinning, weaving, dyeing and finishing of fabrics to the contract production of finished garments. Its portfolio of technical textiles includes the supply of fabrics for seating and soft furnishing on aircraft, vessels and hotels while its flame retardant textiles and clothing are used in industries such as steel, petrochemical, motor-racing and defence. In addition to this a key part of Akin Tekstil's business is its involvement in the supply of fabrics to the fashion industry and the production of finished garments for various leading American and European brands. To ensure that its fabrics are chosen by designers it is important that the company is visible at leading international events in the fashion industry, including Premiere Vision.
Originally published in Brennan, R., Canning, L., & McDowell, R. (2014). Being Fashion Smart. Business-to-business marketing.(3rd ed., pp. 200-202). London: SAGE Publications Ltd. Print. ISBN: 9781446273722.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Akin Tekstil; Textile industry -- Turkey